Novel microcalorimetric assay for antibacterial activity of implant coatings: The cases of silver‐doped hydroxyapatite and calcium hydroxide. Issue 6 (7th October 2014) - Braissant, Olivier; Chavanne, Philippe; de Wild, Michael; Pieles, Uwe; Stevanovic, Sabrina; Schumacher, Ralf; Straumann, Lukas; Wirz, Dieter; Gruner, Philipp; Bachmann, Alexander; Bonkat, Gernot
Abstract Biomaterials with antimicrobial properties are now commonly used in different clinical specialties including orthopedics, endodontic, and traumatology. As a result, assessing the antimicrobial effect of coatings applied on implants is of critical importance. In this study, we demonstrate that isothermal microcalorimetry (IMC) can be used for monitoring bacterial growth and biofilm formation at the surface of such coatings and for determining their antimicrobial effects. The antibacterial effects of silver doped hydroxyapatite (HA) and calcium hydroxide coatings on Staphylococcus epidermidis were determined with a minimal workload. Using the Gompertz growth model we determined biofilm growth rates close to those values reported in the literature. Furthermore, we were able to estimate the reduction in the bacterial inocula originally applied at the surface of the coatings. Therefore, in addition to monitoring the antimicrobial effect of silver doped HA and calcium hydroxide coatings, we also demonstrate that IMC might be a valuable tool for assessing such antimicrobial properties of implant coatings at a minimal workload. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1161–1167, 2015.